The Emergence of the Residents’ Belief in the Existence of Gembel Children in Dieng Plateau Area - Sahid Sahid (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2020)
This study aims at analysing the emergence of Javanese’s belief and attitudes in the existence of gembel children among the residence of Dieng Plateau Area. This study focuses on two villages to be observed, Dieng Village (Eastern Dieng) that belongs to Wonosobo Regency and Dieng Kulon Village that belongs to Banjarnegara Regency. The researcher conducts in-depth interview, observation and also documentation toward the stake holders (residents, traditional leader, gembel children). The result is that the existence of them (gembel children) are very important to the residents, they also have the great attitudes toward them (gembel children). Some believes also emerge among the residents of these two villages as a result of their existence (gembel children).